2023
DOI: 10.3390/nu15132879
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Manipulation of Amino Acids for Cancer Therapy

Abstract: Cancer cells cannot proliferate and survive unless they obtain sufficient levels of the 20 proteinogenic amino acids (AAs). Unlike normal cells, cancer cells have genetic and metabolic alterations that may limit their capacity to obtain adequate levels of the 20 AAs in challenging metabolic environments. However, since normal diets provide all AAs at relatively constant levels and ratios, these potentially lethal genetic and metabolic defects are eventually harmless to cancer cells. If we temporarily replace t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 371 publications
0
3
0
Order By: Relevance
“…However, due mostly to reasons provided in Section 10.2. above, only perfunctory attention has been accorded the GTωA pathway (i.e., L-glutamine KGM → α-ketoglutarate). Several authors (e.g., [158][159][160][161]) have quoted our work that demonstrates GLS1 protein/activity is increased in aggressive prostate cancer cells (cf., [1]), but neglected to provide the rationale associated with the upregulation of the GTωA pathway in these cells. This omission resulted in providing only partial understanding of the integrative relationship between the GTωA and canonical pathways for conversion of L-glutamine to α-ketoglutarate, particularly in cancerous tissues.…”
Section: Possible Role Of Glutamate Dehydrogenase (Gdh) In the Produc...mentioning
confidence: 97%
“…However, due mostly to reasons provided in Section 10.2. above, only perfunctory attention has been accorded the GTωA pathway (i.e., L-glutamine KGM → α-ketoglutarate). Several authors (e.g., [158][159][160][161]) have quoted our work that demonstrates GLS1 protein/activity is increased in aggressive prostate cancer cells (cf., [1]), but neglected to provide the rationale associated with the upregulation of the GTωA pathway in these cells. This omission resulted in providing only partial understanding of the integrative relationship between the GTωA and canonical pathways for conversion of L-glutamine to α-ketoglutarate, particularly in cancerous tissues.…”
Section: Possible Role Of Glutamate Dehydrogenase (Gdh) In the Produc...mentioning
confidence: 97%
“…Dietary restriction of protein and certain amino acids, including serine, methionine, and branched-chain amino acids (BCAAs) such as leucine, isoleucine, and valine, has been shown to impede tumor growth. 159 One mechanism through which protein restriction may inhibit tumor growth is via the IGF-1 signaling pathway. In melanoma and breast cancer mouse models, it has been observed that mice fed a low-protein diet (4% kcal protein) exhibit reduced IGF-1 levels and slower tumor progression compared to those fed a high-protein diet (18% kcal protein).…”
Section: Targeted Dietary Interventions and Mechanistic Insights Into...mentioning
confidence: 99%
“…above, only perfunctory attention has been accorded the GTωA pathway (i.e., l -glutamine ⇆ KGM → α-ketoglutarate). Several authors (e.g., [ 158 , 159 , 160 , 161 ]) have quoted our work that demonstrates GLS1 protein/activity is increased in aggressive prostate cancer cells (cf., [ 1 ]), but neglected to provide the rationale associated with the upregulation of the GTωA pathway in these cells. This omission resulted in providing only partial understanding of the integrative relationship between the GTωA and canonical pathways for conversion of l -glutamine to α-ketoglutarate, particularly in cancerous tissues.…”
Section: Glutaminase II (Gtωa) Pathway Enzymes In Cancermentioning
confidence: 99%